2013
DOI: 10.1371/journal.pone.0071548
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding and School Attainment in Five Cohorts from Low- and Middle-Income Countries

Abstract: BackgroundPerformance in intelligence tests tends to be higher among individuals breastfed as infants, but little is known about the association between breastfeeding and achieved schooling. We assessed the association of infant feeding with school achievement in five cohorts from low- and middle-income countries. Unlike high-income country settings where most previous studies come from, breastfeeding is not positively associated with socioeconomic position in our cohorts, thus reducing the likelihood of a spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 36 publications
(41 reference statements)
0
29
0
2
Order By: Relevance
“…As described by the WHO in 2003, both clinical and population-based research that focuses on findings pertaining to references for international growth are critical to long-term global goals of increasing breastfeeding engagement [11]. Research in this area has only begun to take an international approach towards meeting this goal [1213]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described by the WHO in 2003, both clinical and population-based research that focuses on findings pertaining to references for international growth are critical to long-term global goals of increasing breastfeeding engagement [11]. Research in this area has only begun to take an international approach towards meeting this goal [1213]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the effects and direction of other determinants such as income, parity, mode of delivery, preterm birth, and ethnicity have been less clear across studies [13,3134]. These differences may be attributable to interaction effects with determinants particular to specific cultures or regions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that maternal IQ is a vital confounder, but that the IQ of the mother only partially accounts for the association because even in those studies, which controlled for maternal intelligence, breastfeeding was associated with increased scores on intelligence tests (2.19 IQ points on average) (Horta et al, 2013). Walfisch and co-workers (2013) on the other hand suggested in the most comprehensive meta-analysis to date, that the relationship between breastfeeding and child cognition is mainly due to maternal confounders.…”
mentioning
confidence: 99%
“…Two comprehensive meta-analyses with contrasting results have recently been published (Horta et al, 2013;Walfisch et al, 2013). Horta and Victora (2013) suggested that breastfeeding associated with better outcomes in intelligence tests (with an average of 3.5 points) during childhood/adolescence.…”
mentioning
confidence: 99%
See 1 more Smart Citation